Proto-identidades desde las narrativas institucionales: un ejercicio de encapsulamiento de las identidades flexibles para un tratamiento homogéneo. - Magallanes Payan, José Arturo (2023)
Studies on migrations and migrants are especially aimed at identifying the problems that arise in the journeys from the place of origin and arrival to the planned space, however, they are usually influenced by narratives taken uncritically, in this case from the IOM. The study aims to analyze and identify the metaphors and sentences that reveal a certain ideological-discursive trend related to the so-called Governance in the document Highlights of the 2020 Annual Report offered by this organization. Based on this analysis, concepts were identified that together with others make up a virtuous equation, a process that entails, due to the level of expertise in its composition, an unquestionable degree of veracity, since they are located in what is called politically correct in the multiculturalism. In this way, the IOM narratives create a virtual migrant under the so-called data economy.